Hybrid model of intensive lifestyle intervention is potentially effective in patients with diabetes & obesity for post-COVID era - Dhaver, Shilton; Al-Badri, Marwa; Salah, Tareq; Kilroy, Cara; Shahar, Jacqueline; Johnson, Colleen; Votta, Jennie; Mitchell, Christine; Beaton, Joan; Khater, Abdelrahman; Kibaa, Karim; McCarragher, Ryan; et al. (Frontiers in Endocrinology, 2023)
The Weight Achievement and Intensive Treatment (Why WAIT) program is a 12-week multidisciplinary intensive lifestyle intervention (ILI) for patients with diabetes and obesity in real-world clinical practice that has led to long-term weight loss maintenance for up to 10 years. During COVID-19, we reported that a virtual model (VM) of the program was equally effective in reducing body weight and improving glycemic control. Here, we test a newly-introduced hybrid model (HM), to accommodate ongoing restrictions of the pandemic. We evaluated 56 participants: 18 from HM, 16 from VM, and 22 from the in-person model (iPM). At 12 weeks, the mean change in body weight from baseline for HM was -8.2±5.0 kg; p<0.001. The mean change in A1C for HM was -0.6±0.6%; p=0.002. There were no significant differences in body weight reduction (p=0.7) or A1C reduction (p=0.6) between groups. Blood pressure, lipid profile, and all other parameters showed improvements without significant differences between groups. Overall, HM is as effective as VM and iPM in reducing body weight and A1C after 12 weeks. Given its scalability, HM could be offered to more patients with diabetes and obesity who may benefit from its increased flexibility and enhanced accountability without compromising the multidisciplinary approach for a post-COVID era.